The two crystal structures of unloaded and cargo-loaded Vacuolar Sorting Receptor 1 lumenal domain (VSR1-Nt) reveal two cargo binding sites and a mechanism of transport - Borges, Rafael J.; Eldahshoury, Mahmoud K.; Parr, Rebecca J.; Paul, Marilyn; Fyfe, Paul; Nettleship, Joanne E.; An, Jing; Shah, Nita; Levada, Ana Júlia Loureiro; Fontes, Marcos Roberto de Mattos; Owens, Raymond J.; Denecke, Jurgen; et al. (Cold Spring Harbor Laboratory, 2024)
Abstract Vacuolar sorting receptors (VSRs) are type I membrane proteins crucial for seed germination and plant development. While VSR trafficking has been extensively studied, the mechanism of cargo binding and release by the N-terminal lumenal region is less understood. We have elucidated the crystal structures of unloaded and cargo-loaded forms of the lumenal region of VSR1 containing the protease-associated domain, the Central domain and epidermal growth factor-like repeats. Calcium coordination induces remodeling of the linkers between domains, triggering large conformational changes that expose two binding sites, one across the PA and Central domain and a second site in the Central domain. Our findings provide a mechanistic model for cargo binding in a calcium rich environment, where VSR is locked in a conformation exposing the cargo binding sites, while cargo release is favoured by lower calcium concentrations and trimer formation. These results advance our current knowledge on VSRs and will inform future studies on vacuolar trafficking and cargo binding/release.